PENGARUH DISKRIMINASI HARGA RUMAH SAKIT JAKARTA TERHADAP PELAYANAN TENAGA KESEHATAN UNTUK MENINGKATKAN KESEJAHTERAAN KELUARGA MISKIN - Aminda, Renea Shinta; Asri, Nani; Damanik, Michael Armando; Mawarti, Citra; Fahriza, Dian; Hanifah, Fadya Nur; Humaira, Zahra (JPMUJ, 2024)
This study aims to explore the effect of price discrimination in Jakarta hospitals on health worker services and the welfare of poor families. The research method used is qualitative research with secondary data collection techniques by researching previous research journals. The results of this study show that price discrimination in Jakarta hospitals against poor patients can affect the services of health workers and the welfare of poor families. The price discrimination causes poor patients to not get the same services as rich patients, such as longer waiting times, inadequate care, and lack of attention from health workers. This has an impact on the welfare of poor families who have to spend more money to get proper health care. Therefore, efforts are needed to overcome price discrimination in Jakarta hospitals and improve the services of health workers to improve the welfare of poor families.